Reflexões sobre a formação do leitor mirim: Leitura, Literatura Infantil e Bibliotecas Escolares - Girotto, Cyntia Graziella Guizelim Simões [UNESP] (My University, 2013)
This paper seeks to relate issues to the formation of the reader and school routines that directly interfere in the way responsible for the mediation work there included the act of reading, and also reflect on the pedagogical implications arising therefrom. The resumption of data generated in research developed in the years 2007 to 2010 shows that both the classroom as the school library has been constituted as ambiance suitable for training the child reader. Theoretical and methodological concepts related to child development in the act of reading is presented by discussing access to books and children’s literature led to the formation of the child reader, linking them to the old and new reading technologies.

Este texto procura relacionar questões ligadas à formação do leitor mirim e às rotinas escolares que interferem diretamente no modo como os responsáveis pelas mediações aí inclusas trabalham o ato de ler e, ainda, refletir sobre as implicações pedagógicas delas decorrentes. A retomada de dados gerados em pesquisa desenvolvida nos anos de 2007 a 2010 demonstra que tanto a sala de aula como a biblioteca escolar não têm se constituído como ambiências adequadas à formação da criança leitora. Conceitos teóricometodológicos relacionados ao desenvolvimento infantil no ato de ler são apresentados, mediante a discussão do acesso aos livros e à literatura infantil dirigida à formação da criança leitora, articulandoos às velhas e novas tecnologias de leitura.
Reflections on the formation of the mirim reader: reading, children’s literature and school library